Insight into how cyber forensic accounting enhances the integrated reporting quality in small and medium enterprises - Quang Huy Pham; Kien Phuc Vu (Cogent Business & Management, 2024)
The objective of this current research is to examine the influence of cyber forensic accounting on the quality of integrated reporting. The current investigation employed a mixed-methods approach. As a result, the objective of examining the qualitative viewpoints expressed in the expert interviews was to ascertain the practical implementation of the constructs and gain a more comprehensive understanding of several concerns associated with the proposed model. The proposed model, which was verified using AMOS 28.0 software and structural equation modeling, was empirically supported by the examination of statistical data collected from surveys administered to accountants employed in small and medium-sized businesses. The outcome analyses that were performed identified positive and statistically significant relationships between the hypothesized constructs in terms of effect magnitude. More concretely, among the components of cyber forensic accounting that impacted the quality of integrated reporting, zero trust governance and management control systems exhibited the highest path coefficient, followed by cyber anti-fraud policies. Conversely, digitally designed forensic procedures demonstrated the lowest path coefficient. Furthermore, aside from providing a solid foundation for future investigations, the refined insights presented in this work can also assist policy-makers and practitioners in recognizing and capitalizing on prospects to improve and expand quality of integrated reporting. This can be achieved through the implementation of efficient and effective rules and policies related to cyber forensic accounting management.
Keywords: 650; cybersecurity; integrated reporting; forensic accounting; SME